Opportunities and Challenges Of Peace-Building In The Russia-Ukraine Armed Conflict - Erwin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Armed conflicts between two or more countries seem unavoidable in international relations from the past to the present, including the armed conflict between Russia and Ukraine that has been ongoing since 2022. The discussion in this paper uses a normative method. In terms of efforts to resolve the armed conflict between Russia and Ukraine, there are two main aspects: opportunities and challenges in achieving a mutually beneficial resolution for both parties. The role and efforts can be undertaken by the UN and the international community through various frameworks and mechanisms for the resolution of international disputes, in this case, the armed conflict that has been ongoing since February 2022 between Russia and Ukraine.